Science and Technology Development in Dutch East Indies - Maulana Akbar; Tri Handayani (Diponegoro University, 2021)
This article describes the long history of the development of science and technology in Indonesia under Dutch East Indies Administration. This study views at how education and science and technology policies in together create the development of the contributions of researcher in research institutions. The study uses a convergent model triangulation which is a mixed method in which the qualitative use the archive to find comprehensive traces taken through written sources, quantitative method and bibliometric to show how research networks are formed in producing research from 1849 until 1940, especially on research topics. This study collects data from 201 scientific articles from Scopus database to obtain information about the trends of Dutch East Indies scientific publication. The findings of this study are after ethical politics in the beginning of 21 century, colonial government failed to provide more inclusive education system for all groups. Therefore, the scientist who contributed are mainly from European group and small contribution of Indonesian in the medical field. In the national context, there were an incline number of scientific publications after 1920s that is contributed from the established a wide range of government research and development institutions the decades before. After the colonial government ended in 1941, these advantages became the initial foundation of science and technolgy ecosystem in Republic of Indonesian Government.